Unravelling the structural rearrangement of polymer colloidal crystals under dry sintering conditions. Issue 33 (10th August 2018) - Zozulya, Alexey V.; Zaluzhnyy, Ivan A.; Mukharamova, Nastasia; Lazarev, Sergey; Meijer, Janne-Mieke; Kurta, Ruslan P.; Shabalin, Anatoly; Sprung, Michael; Petukhov, Andrei V.; Vartanyants, Ivan A.
Abstract : The structural rearrangement of polystyrene colloidal crystals under dry sintering conditions has been revealed by in situ grazing incidence X-ray scattering. Abstract : The structural rearrangement of polystyrene colloidal crystals under dry sintering conditions has been revealed by in situ grazing incidence X-ray scattering. The measured diffraction patterns were analysed using distorted wave Born approximation (DWBA) theory and the structural parameters of the as-grown colloidal crystals of three different particle sizes were determined for the in-plane and out-of-plane directions in a film. By analysing the temperature evolution of the diffraction peak positions, integrated intensities, and widths, the detailed scenario of the structural rearrangement of crystalline domains at the nanoscale has been revealed, including thermal expansion, particle shape transformation and crystal amorphisation. Based on DWBA analysis, we demonstrate that in the process of dry sintering, the shape of colloidal particles in a crystal transforms from a sphere to a polyhedron. Our results deepen the understanding of the thermal annealing of polymer colloidal crystals as an efficient route for the design of new nano-materials.